1997
DOI: 10.1021/om960996f
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Studies of Inorganic and Organometallic Reaction Mechanisms. 10. Reversal in Stability of Rhodium and Iridium η2-Ethene and Hydridovinyl Complexes

Abstract: Ab initio quantum mechanical calculations were used to examine models for the reaction [η 3 -HB(X) 3 ](CO)M(η 2 -CH 2 CH 2 ) f [η 2 -HB(X) 3 ](CO)M(η 2 -CH 2 CH 2 ) f [η 3 -HB(X) 3 ](CO)M(H)-(CHCH 2 ), for which it is known that the equilibrium lies toward the hydridovinyl product for iridium, with X ) 3-trifluoromethyl-5-methylpyrazol-1-yl, and lies toward the η 2 -ethene reactant for rhodium, with X ) 3,5-dimethylpyrazol-1-yl, and most other related systems. The ligand models tested correspond to X ) NHNH 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 29 publications
1
22
0
Order By: Relevance
“…Recently, published theoretical work on the rearrangement of (η 3 -Tp)M(CO)(η 2 -CH 2 CH 2 ) to (η 2 -Tp)M(CO)(η 2 -CH 2 CH 2 ) (M = Rh, Ir) shows that both the η 3 -Tp and the η 2 -Tp ethane complexes are stable species connected by a small barrier. The subsequent reaction of these species to the oxidative-addition product (η 3 -Tp)M(CO)(H)(CHCH 2 ) proceeds through a single transition state from both of the ethane isomers.…”
mentioning
confidence: 99%
“…Recently, published theoretical work on the rearrangement of (η 3 -Tp)M(CO)(η 2 -CH 2 CH 2 ) to (η 2 -Tp)M(CO)(η 2 -CH 2 CH 2 ) (M = Rh, Ir) shows that both the η 3 -Tp and the η 2 -Tp ethane complexes are stable species connected by a small barrier. The subsequent reaction of these species to the oxidative-addition product (η 3 -Tp)M(CO)(H)(CHCH 2 ) proceeds through a single transition state from both of the ethane isomers.…”
mentioning
confidence: 99%
“…This dissimilarity may be a reflection of the differences in C−H bond activation mechanistic pathways as discussed below, and this divergence may rely on the thermodynamic stabilities of oxidation states I and III for Rh and Ir. As mentioned earlier in this paper, for the former element the monovalent state is relatively favored …”
Section: Resultsmentioning
confidence: 52%
“…Whereas the Ir(I)(η-C 2 H 4 ) formulation may be in some cases (e.g., in complexes of the Tp‘ ligands) thermodynamically less favorable than the corresponding Ir(III)H(CHCH 2 ) isomers, for Rh, Rh(III)H(CHCH 2 ) compounds are thermally unstable with respect to Rh(I)(η-C 2 H 4 ), irrespective of the nature of the auxiliary ligand (Cp‘ or Tp‘). The reasons for this are mostly (or exclusively) electronic and reflect the higher tendency of the 5d vs the 4d transition metals to undergo oxidation−addition reactions …”
Section: Introductionmentioning
confidence: 99%
“…Despite this general viewpoint, Bergman showed that thermolysis of Cp­(PMe 3 ) 2 Re­(H)­( n -hexyl) induced reductive elimination of hexane followed by subsequent reaction of Cp­(PMe 3 ) 2 Re with ethylene that resulted in a 10:1 mixture of the Re-vinyl hydride ( I ) to the Cp­(PMe 3 ) 2 Re­(η 2 -ethylene) π-complex ( II , Scheme b) . A similar observation was also reported for Fe­(depe) 2 , and Ir/Rh complexes with pyrazolylborate or Cp* ligands. , Critically important for the Re reaction, the π-complex is thermodynamically more stable than the Re-vinyl hydride and therefore there is no conversion from the π-complex II to the Re-vinyl hydride I . This result indicates that the π-complex is not required in the mechanism to achieve the Re-vinyl hydride.…”
Section: Introductionmentioning
confidence: 58%